Incidence and body location of reported acute sports injuries in seven sports using a national insurance database - Aaman, M.; Forssblad, M.; Larsen, K. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Sports with high numbers of athletes and acute injuries are an important target for preventive actions at a national level. Both for the health of the athlete and to reduce costs associated with injury. The aim of the present study was to identify injuries where injury prevention should focus, in order to have major impact on decreasing acute injury rates at a national level. All athletes in the seven investigated sport federations (automobile sports, basketball, floorball, football (soccer), handball, ice hockey, and motor sports) were insured by the same insurance company. By using this insurance database, the incidence and proportion of acute injuries, and injuries leading to permanent medical impairment (PMI), at each body location, was calculated. Comparisons were made between sports, sex and age. In total, there were 84754 registered injuries during the study period (year 2006-2013). Athletes in team sports, except in male ice hockey, had the highest risk to sustain an injury and PMI in the lower limb. Females had higher risk of injury and PMI in the lower limb compared to males, in all sports except in ice hockey. This study recommends that injury prevention at national level should particularly focus on lower limb injuries. In ice hockey and motor sports head/neck and upper limb injuries also need attention.